Influence of surface nitridation and an AlN buffer layer on the growth of GaN nanostructures on a flexible Ti metal foil using laser molecular beam epitaxy. (17th May 2019) - Ramesh, Chodipilli; Tyagi, Prashant; Gupta, Govind; Kumar, Muthusamy Senthil; Kushvaha, Sunil Singh
Abstract: GaN nanorods (NRs) and hollow nanocolumns (HNCs) were grown on flexible Ti foils using laser-assisted molecular beam epitaxy at a growth temperature of 700 °C. The shape, size and density of the GaN nanostructures were tuned by surface nitridation and AlN buffer layer growth temperature on a Ti foil. Sparse (∼ 5.5 × 10 8  cm −2 ) GaN NRs were obtained on the bare surface whereas dense (∼3.47 × 10 9  cm −2 ) GaN NRs were grown on the nitridated Ti foil. The shape of the GaN changed from NRs to HNCs by introducing an AlN buffer layer on nitridated Ti foil. Raman spectroscopy showed the grown GaN nanostructures have a wurtzite crystal structure. Room-temperature photoluminescence spectroscopy measurements show that the GaN nanostructures possess an intensive near band edge emission at ∼3.42 eV with a negligible defect-related peak. The growth of tunable GaN nanostructures on flexible metal foils is attractive for flexible optoelectronics and sensor devices.